Antioxidant Activity of an Aqueous Extract of Cuttlefish Ink during Fish Muscle Heating - Marcos Trigo; David Paz; Antía Bote; Santiago P. Aubourg (MDPI AG, 2023)
The antioxidant effect of cuttlefish (Sepia officinalis) ink (CFI) was analysed in the present study. A model system consisting of minced seabream (Sparus aurata) muscle and different concentrations of an aqueous extract of CFI was subjected to a heat (50 °C) treatment for 12 days. The effects of the CFI content and the heating time on lipid oxidation (conjugated diene (CD), conjugated triene (CT), and peroxide values and fluorescent compound formation), hydrolysis (free fatty acid content) development, and changes in the fatty acid (FA) profile (polyene index (PI), unsaturated FA content, ω3/ω6 ratio) were determined. The addition of the aqueous extract of CFI led to a lower (p < 0.05) development of lipid oxidation (CD, CT, and fluorescent compound determination) and to a higher (p < 0.05) retention of unsaturated FAs (PI determination). More important effects were found with increased CFI concentrations and at advanced heating times. However, a definite effect on lipid hydrolysis development (FFA value) could not be inferred. A new approach for the beneficial use of cuttlefish ink is presented. According to the direct relationship between rancidity stability and nutritional and sensory values, the present study provides a new strategy for the quality enhancement of thermally treated seafood.